Pengaruh ROA, LDR, Ukuran Perusahaan, CAR, NPL terhadap Return Saham pada Perusahaan Perbankan di BEI - Ni Putu Mia Pradnyawati; Ni Luh Gede Novitasari; Ni Luh Putu Widhiastuti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The purpose of this study is to find out ROA, LDR, Company Size, CAR and NPL on Stock Returns at Banking Companies listed on the IDX in 2019-2021. The data collection method used in this research is documentation. The method of determining the sample of this research is purposive sampling. The number of samples from this study were 41 samples with a total sample of 123 observations. The data analysis technique used was multiple linear regression analysis. The results of this study are ROA, LDR, CAR have a positive effect on Stock Returns, Company size has no effect on Stock Returns and NPL has a negative effect on stock returns. Several banking companies listed on the Indonesia Stock Exchange (IDX) should publish more complete financial reports and accessible to the public so that it can facilitate potential investors in assessing financial performance and making decisions about choosing stocks that are in accordance with their perceptions. Based on the adjusted R square value of 56.0%, there is still 44.0% of other variables that can be used for further research such as: Price Earning Ratio, current ratio, Total Asset Turnover, Net Profit Margin, and debt to equity ratio.